Improving animal welfare in wildlife shooting: The importance of projectile energy. (22nd October 2016) - Hampton, Jordan O.; Adams, Peter J.; Forsyth, David M.; Cowled, Brendan D.; Stuart, Ivor G.; Hyndman, Tim H.; Collins, Teresa
ABSTRACT: In wildlife shooting programs, the energy profile of the projectile or bullet (i.e., kinetic energy transferred to the animal), as distinct from caliber (projectile diameter), is an important factor for animal welfare. We examined the role of projectile energy in determining animal welfare outcomes for a typical European rabbit ( Oryctolagus cuniculus ) sharpshooting program. We compared 2 projectiles of different energy profiles: low‐energy 40‐grain .22 long rifle rimfire (.22LR; 198 J) bullets and high‐energy 40‐grain .222 Remington® centerfire (.222R; 1, 433 J) bullets, fired under similar conditions on 3 nights in September 2014, on a livestock grazing property near Broken Hill, New South Wales, southeastern Australia. We used a thermal‐imaging camera to collect antemortem data from 500 rabbits that were shot at varying distance. We collected postmortem data via visual inspection from 482 rabbits that were killed. We used these data to compare 3 animal welfare parameters: wounding rate, duration of suffering, and ballistic injuries. We then used regression modeling to measure the effect of projectile type on these welfare parameters while accounting for shooting distance. All animal welfare parameters indicated that .222R projectiles were more humane than .22LR projectiles. When controlling for distance, for rabbits shot with a .22LR compared with a .222R, the odds of nonlethal wounding increased by a factor of 8 and noninstantaneous death increased by a factor of 9. All animal welfare parameters declined with increasing distance for both projectiles. Our results show that projectile energy and shooting distance were critical determinants of animal welfare outcomes in wildlife shooting programs. © 2016 The Wildlife Society. Abstract : Animal welfare outcomes may be influenced by many factors in wildlife shooting programs. By comparing 2 different shooting configurations used for the control of European rabbits, we demonstrated that projectiles with greater kinetic energy can generate superior animal welfare outcomes.